Alteration of transcriptomic networks in adoptive-transfer experimental autoimmune encephalomyelitis - Iacobas, Dumitru A.; Iacobas, Sanda; Werner, Peter; Scemes, Eliana; Spray, David C. (Frontiers in Integrative Neuroscience, 2007)
Adoptive transfer experimental autoimmune encephalomyelitis (AT-EAE) is an inflammatory demyelination that recapitulates in mouse spinal cord (SC) the human multiple sclerosis disease. We now analyze previously reported cDNA array data from age-matched young female adult control and passively myelin antigen-sensitized EAE mice with regard to organizational principles of the SC transcriptome in autoimmune demyelination. Although AT-EAE had a large impact on immune response genes, broader functional and chromosomal gene cohorts were neither significantly regulated nor showed significant changes in expression coordination. However, overall transcriptional control was increased in AT-EAE and the proportions of transcript abundances were perturbed within each cohort. Striking likenesses and oppositions were identified in the coordination profiles of genes related to myelination, calcium signaling, and inflammatory response in controls that were substantially altered in AT-EAE. We propose that up- or down-regulation of genes linked to those targeted by the disease could potentially compensate for the pathological transcriptomic changes.